ANALISIS TRANSMISSION OF MONETERY POLICY TERHADAP PERTUMBUHAN EKONOMI DAN KEUANGAN PASCA PEMULIHAN EKONOMI IN FIVE APEC COUNTRIES - Zebua, Alexander; Nasution, Lia Nazliana (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The aim of this research is to determine and investigate how the global economic crisis in 2020 affected financial and economic growth after the Covid-19 crisis and the economic recovery that followed. Secondary data covering the period 2013 to 2023 was used in this research. Money supply, real interest rates, exchange rates, investment, inflation, and gross domestic product are the variables taken into account. This research examines the short-term and long-term impacts of monetary policy on financial and economic growth in five Asia Pacific Economic Cooperation (APEC) countries using the Structural Vector Autoregressive (SVAR) approach. Three variables investment, reallinteresttrates, and moneyxsupplyido not significantly influence1economicxor financial growth, according to the study's findings, while two variables inflation and exchange rates have a positive impact on economic and financial growth.